Implementation of the Minimum Initial Service Package (MISP) as an Effort to Fulfill Reproductive and Sexual Health Services in Disaster Situations: Systematic Review - Efa Nugroho; Alfiana Ainun Nisa; Rafidha Nur Alifah; Bambang Budi Raharjo; Annisa Novanda Maharani Utami; Dwi Yunanto Hermawan (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Background: The Minimum Initial Service Package (MISP) was developed as a guideline for implementing reproductive health services in disaster situations. However, there have not been many studies that comprehensively assess the implementation of all components of the MISP in disaster situations. This study provides an overview and evaluates the implementation of the eight components of the MISP in various countries. Methods: This research was a systematic review that gathered several studies using the PRISMA flow. Using relevant keywords, the researcher obtained studies from PubMed, Science Direct, and Scopus databases. Studies were collected from April to June 2024. Results: The findings of this research highlight the importance of strengthening coordination, communication, training, advocacy, comprehensive implementation strategies, and targeted interventions to maximize the effectiveness of the MISP in disaster response efforts. Our research offers a robust empirical basis to reformulate MISP policies, directly contributing to greater investment in healthcare, with a particular focus on emergency response. Conclusion: In conclusion, our study contributes to the understanding of reproductive sexual and health issues in disaster setting by evaluating the implementation of the Minimum Initial Service Package (MISP). This research provides insights into the implementation of MISP in various disaster context across different countries. Future studies should focus on evaluating the effectiveness of the MISP to further advance knowledge in the field of international health.